2000
DOI: 10.1104/pp.124.3.1019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rice Varieties with High Tolerance or Sensitivity to Lead and Characterization of the Mechanism of Tolerance

Abstract: Pb inhibits plant growth. To study Pb tolerance in rice (Oryza sativa), we screened 229 varieties for Pb tolerance or sensitivity. Three-day-old seedlings were treated for 12 d with 20 m Pb solution. Based on the dry weight of the root, three var Kumnung) and three Pb-sensitive (var Aixueru, var C-9491, var Milyang23) rice varieties were selected. The root biomasses of the tolerant varieties were approximately 10-fold higher than those of the sensitive ones. The greatest morphological difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(116 citation statements)
references
References 18 publications
4
108
2
2
Order By: Relevance
“…The trend in observations were found in agreement with the previous work of various researchers for different rice varieties (Mishra and Choudhuri, 1998;Yang et al, 2000;Verma and Dubey, 2003), cereals (Mahmood et al, 2007), castor bean (Romeiro et al, 2006), maize (Gupta et al, 2009) and willows (Zhivotovsky et al, 2011). In response to Pb absorption, root growth was reduced and branching pattern was changed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The trend in observations were found in agreement with the previous work of various researchers for different rice varieties (Mishra and Choudhuri, 1998;Yang et al, 2000;Verma and Dubey, 2003), cereals (Mahmood et al, 2007), castor bean (Romeiro et al, 2006), maize (Gupta et al, 2009) and willows (Zhivotovsky et al, 2011). In response to Pb absorption, root growth was reduced and branching pattern was changed.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, rice straw is used for livestock feed and bedding that may indirectly become a human health risk, if having high Pb and As in flooded soil contaminated by lead arsenate pesticide (Codling, 2009). In literature, a very few reports are available regarding the genetic variability among rice genotypes to produce low Pb rice from Pb-polluted soil conditions (Yang et al, 2000;Verma and Dubey, 2003). For a wide range of soils, selecting and growing low Pb accumulating rice genotypes/varieties can be a wise choice.…”
Section: Introductionmentioning
confidence: 99%
“…Shaheen basmati might have adopted avoidance mechanism for reduce metal uptake by chelate secretion or deposition in cell wall components (Meharg, 2005). Yang et al (2000) found that tolerant rice varieties regulate oxalate synthesis and secretion that precipitates Pb; thus decreasing its uptake by plant roots. Previous studies have also shown that concentration of Pb in rice plants grown on Pbcontaminated soil was positively correlated with the total soil Pb concentration (Yang et al, 2004) and that the concentration of Pb in shoots of Atriplex halimus increased with the level of applied Pb in a growth medium in the presence of NaCl (Kadukova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Under heavy metal contamination conditions, when roots of two plant species close or touch, the phenomenon of "rhizosphere talk" could produce between two plant spaces, which could promote or inhibit plant growth and heavy metal accumulation [3][4][5]. When hyperaccumulator Sedum alfredii intercrops with common plants maize and ryegrass respectively, the Zinc (Zn) accumulation in S. alfredii increase significantly, and cadmium (Cd) and Zn contents in maize and ryegrass reduce significantly [6].…”
Section: Introductionmentioning
confidence: 99%